2016
DOI: 10.1021/jacs.6b08787
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Time-Dependent Surface-Enhanced Raman Spectroscopy, Metabolomics, and Proteomics Reveal Cancer Cell Death Mechanisms Associated with Gold Nanorod Photothermal Therapy

Abstract: In cancer plasmonic photothermal therapy (PPTT), plasmonic nanoparticles are used to convert light into localized heat, leading to cancer cell death. Among plasmonic nanoparticles, gold nanorods (AuNRs) with specific dimensions enabling them to absorb near-infrared laser light have been widely used. The detailed mechanism of PPTT therapy, however, still remains poorly understood. Typically, surface-enhanced Raman spectroscopy (SERS) has been used to detect time-dependent changes in the intensity of the vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 72 publications
3
101
0
Order By: Relevance
“…After PEG modification, the AuNRs became negatively charged (-10.2 ± 6.73 mV) and then became positive again after further modification of the RGD peptides. The characterization results are consistent with previous reports (52,53), which indicates the successful conjugation of the RGD peptides to the surface of AuNRs.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…After PEG modification, the AuNRs became negatively charged (-10.2 ± 6.73 mV) and then became positive again after further modification of the RGD peptides. The characterization results are consistent with previous reports (52,53), which indicates the successful conjugation of the RGD peptides to the surface of AuNRs.…”
Section: Resultssupporting
confidence: 91%
“…The proteomics analysis was conducted using the previously reported method (53). Briefly, purified and dried peptide samples from the previous step were dissolved in 10 μL solvent with 5% acetonitrile and 4% FA, and 4 μL of the resulting solutions were loaded onto a microcapillary column packed with C18 beads (Magic C18AQ, 3 μm, 200 Å, 100 μm × 16 cm, Michrom Bioresources) by a Dionex WPS-3000TPLRS autosampler (UltiMate 3000 thermostated Rapid Separation Pulled Loop Well Plate Sampler).…”
Section: Methodsmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) can be formulated in different shapes such as nanospheres, nanorods, nanoshells, nanostars, and nanocages because they exhibit excellent size and shape tunability and physiochemical properties [42]. Although AuNPs illustrate different shapes, all possess certain unique properties such as biological inertness and biocompatibility, the ability to absorb high energy X-rays, and they can be fine-tuned to absorb light in the near infra-red region (700–1200 nm) due to inherent SPR [43]. Considerable progress has been made towards the development of NIRF sensitive nanoparticles for efficient cancer imaging, identification of residual cells during surgery, and for locating the surgical margins [44].…”
Section: Imaging and Photo-thermal Therapy Using Gold Nanoparticlesmentioning
confidence: 99%
“…More accurate information of PTT was given by MS identification of chemical species responsible for specific SERS signals. It was discovered that phenylalanine metabolism was perturbed upon PTT, causing irregular levels of phenylalanine and its derivative molecules, which induced cellular apoptosis (Figure B) . Hyperoxia‐induced biomolecular modifications were studied by SERS in neonatal mouse lung fibroblasts (nMLF), and Raman vibrations corresponding to phenylalanine and type 1 collagen indicated that hyperoxia induced intracellular acidification in nMLF …”
Section: Sers For Intracellular Detectionmentioning
confidence: 99%